The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.aju.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognosis of intravesical recurrence after surgical management of upper tract urothelial carcinoma: A 30-year single centre experience

Abstract: ObjectiveTo review the incidence, predictors and prognosis of bladder cancer recurrence after management of upper tract urothelial carcinoma (UTUC).Patients and methodsWe retrospectively reviewed patients who were surgically treated for UTUC from 1983 to 2013. The tumours were categorised according to the 1997 Tumour-Node-Metastasis (TNM) staging and the three-tiered World Health Organization grading systems. The primary endpoint was the occurrence of any intravesical recurrence after treatment. We studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
(42 reference statements)
3
6
0
1
Order By: Relevance
“…However, similar to our results, another study reported no significant association between sex and CSS (HR 1.050, 95% CI 0.841‐1.310, Table for OS) . Some studies have shown that CIS is a significant adverse prognostic factor, whereas others have not . As for the BMI, different version existed on the prognostic significance of survival in UTUC that obese UTUC patients had significantly worse CSS than the other three BMI groups ( P = 0.031).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, similar to our results, another study reported no significant association between sex and CSS (HR 1.050, 95% CI 0.841‐1.310, Table for OS) . Some studies have shown that CIS is a significant adverse prognostic factor, whereas others have not . As for the BMI, different version existed on the prognostic significance of survival in UTUC that obese UTUC patients had significantly worse CSS than the other three BMI groups ( P = 0.031).…”
Section: Discussionsupporting
confidence: 83%
“…2 Some studies have shown that CIS is a significant adverse prognostic factor, 3 whereas others have not. 27,28 As for the BMI, different version existed on the prognostic significance of survival in UTUC that obese UTUC patients had significantly worse CSS than the other three BMI groups (P = 0.031). The association between surgical technique, such as laparoscopic RNU, and survival outcome has been debated, and several meta-analyses have shown no significant differences in oncological outcome including IVRFS, CSS, OS, and metastasis rates based on surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…IVR usually develop in up to 50% of patients during surgical follow-up after RNU ( 12 ) with cumulative incidence rates at 1 and 5 years after treatment as high as 31.0% and 48.4%, respectively, in one series ( 24 ), the most frequent site being around the excised bladder cuff. Furthermore, post-surgical IVR may be a significant predictor of later urethral recurrence ( 25 ). In order to find parameters able to predict the outcome of such IVRs, Tanaka et al examined a series of 241 IVRs after RNU for UTUC; according to their analysis, multiplicity, pT1 stage, concomitant carcinoma in situ (CIS) and lack of BCG treatment were independent risk factors for subsequent IVR and/or progression ( 24 ).…”
Section: Post-utuc Nmibcs: Are They Really Different and Why?mentioning
confidence: 99%
“…Çalışmamız, yaş ortalaması 62,6±11,4 yıl olan 16 erkek ve altı kadın hastadan oluşmakta idi. On üç hastanın tümörü sadece renal pelviste, altı hastanın tümörü üreterde bulunmaktaydı ve geri kalan üç hastada multifokal tümör mevcuttu.…”
Section: Bulgularunclassified